Prostate cancer and hypofractionation: reflections on recent randomised phase III clinical trial results - Dearnaley, David; Hall, Emma (Translational Andrology and Urology, 2017)
Four large randomised controlled trials testing modest hypofractionation for localised prostate cancer have reported efficacy and side effect outcomes within the last year (1-8).